Examining the Impact of Proximate Culpability Mitigation in Capital Punishment Sentencing Recommendations: The Influence of Mental Health Mitigators - Gillespie, Lane Kirkland (American journal of criminal justice, 2014)
In spite of the ruling in Atkins v. Virginia ( 2002 ), concerns remain that individuals with mental illness and reduced capacity are eligible for the death penalty. When mental illness or reduced capacity is not enough to preclude death-eligibility, these factors are often discussed at the sentencing phase as mitigators. Mitigation remains an under-researched avenue in the sentencing literature, particularly when it comes to the influence of specific types of mitigation. The present study contributes to knowledge on mental health mitigation by examining five mitigators relevant to the mental health and capacity of defendants. Using data from 834 capital sentences in North Carolina, the influence of these proximate culpability mitigators on jury sentence recommendations is examined. Results indicate that acceptance of certain mental health mitigators reduces the probability of death, but acceptance of others is not significantly related to death recommendations. These findings and their implications are discussed.